Decomposing pay gaps across the wage distribution: investigating inequalities of ethno-religious groups and disabled people - Simonetta Longhi; Cheti Nicoletti; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper provides a contemporary account of inequalities in pay of disabled people and those from selected minority ethno-religious groups. We aim to understand the causes for differences in pay by ethno-religious group and disability status and type. We investigate whether pay gaps are a consequence of individual earning potential as represented, for example, by educational qualifications, or whether they appear to stem from the particular occupations or types of occupation that the minority groups are concentrated into; or whether they are largely unaccounted for. In the case of remaining unexplained gaps in pay, we consider how far they might provide evidence of employer discrimination.
Keywords: 330